A new species of Macrobrachium (Decapoda, Palaemonidae) from Vamanapuram River, Southern Kerala, India - Pillai, P. M.; Unnikrishnan, V. (Zootaxa, 2012)
Macrobrachium prabhakarani new species is described from the Vamanapuram River, Kerala, S. India. The species sharescertain characters with M. scabriculum and M. madhusoodani, while it differs remarkably from these two species in dis-tinctive diagnostic characters: rostral formula 12–14/1–2 with 5–7 postorbital teeth; carapace smooth with distal end ofrostrum directed forwards; chelae with nine denticles in the movable and six in the proximal part of the immovable finger.In larger second chelate leg, merus is longer than carpus and ischium, and propodus is the longest podomere. Carpus and ischium, equal in length and they are the shortest podomeres. Merus and dactylus are also of equal length.